PEYULUHAN DAN PENDAMPINGAN PENGGUNAAN SISTEM MEDIA SOSIAL IBU-IBU RUMAH TANGGA DALAM MENINGKATKAN OMSET PENJUALAN PRODUK CEMILAN KHAS NUSANTARA DI DESA SUKA MAJU KECAMATAN SUNGGAL KABUPATEN DELI SERDANG SUMATERA UTARA - Khamo Waruwu; Elyani; Imam Rangga Bakti; Mella Yunita; Uswatun Hasanah (Universitas Methodist Indonesia, 2021)
The purpose of implementing this community service activity is as a form of concern for house wives who do not know the benefits of using social media as a means to increase sales turnover to increase income, so hereby we are Lecturers of the Faculty of Economics, Faculty of Law and Faculty of Engineering. Tjut Nyak Dhien University tries to innovate and be creative in terms of using the promotion system through Social Media in increasing sales turnover of snack products produced by housewives so that connoisseurs of archipelago snacks can attract consumers with the introduction of Indonesian snacks through social media creativity and innovation in the use of social media are also efforts to develop snack products starting from attractive packaging, variations in flavors that can arouse people's tastes. In terms of increasing sales turnover, we will use Social Media System networks such as: Facebook, Istagram, Whatsapp and Telegram. With this kind of activity, it is expected to help sales indirectly so that it affects the level of turnover and income for housewives who produce household snacks, especially Sunggal District, Deliserdang Regency, North Sumatra and in general and increase people's confidence to become entrepreneurs